ATF2-Induced Overexpression of lncRNA LINC00882, as a Novel Therapeutic Target, Accelerates Hepatocellular Carcinoma Progression via Sponging miR-214-3p to Upregulate CENPM - Ren, Hua; Wei, Zhi-cheng; Sun, Yan-xia; Qiu, Chun-yan; Zhang, Wen-jue; Zhang, Wei; Liu, Tao; Che, Xu (Frontiers in Oncology, 2021)
Background Long intergenic non-protein coding RNA 882 (LINC00882) are abnormally expressed in several tumors. Our research aimed to uncover the functions and the potential mechanisms of LINC00882 in hepatocellular carcinoma (HCC) progression. Methods RT-qPCR was applied to identify LINC00882 and miR-214-3p levels in HCC specimens and cells. Luciferase reporter was applied for the exploration of whether activating transcription factor 2 (ATF2) could bind to the promoter region of LINC00882. Cell proliferation, invasion, and migration were evaluated. In vivo tumor xenograft models were constructed to assess tumorigenicity. RT-PCR, Western blot and Luciferase reporter assays were conducted to examine the regulatory relationships among LINC00882, miR-214-3p and ATF2. Results LINC00882 was markedly upregulated in HCC cells and clinical specimens. Additionally, ATF2 could bind directly to the LINC00882 promoter region and activate its transcription. Loss-of-function studies further demonstrated that LINC00882 knockdown inhibited proliferation, invasion, and migration of HCC cells. Mechanistically, LINC00882 adsorbed miR-214-3p, thus promoting the expressions of CENPM. Rescue assays demonstrated that functions of LINC00882 deficiency in HCC cells were reversed through suppressing miR-214-3p. Conclusion Our group identified a novel regulatory axis of ATF2/LINC00882/miR-214-3p/CENPM, which may provide potential therapeutic targets for HCC.